IMproving psYchosocial adjustment to Traumatic Brain Injury from acute to chronic injury through development and evaluation of the myTBI online psychoeducation platform: protocol for a mixed-methods study - Angelita Martini; Lakkhina Troeung; Colin MacLeod; Georgina Mann; Janet Wagland; Thilaga L Sarunga Raja (BMJ Open)
Introduction This protocol describes the myTBI study which aims to: (1) develop an online psychoeducation platform for people with traumatic brain injury (TBI), their family members/caregivers, and healthcare staff to improve psychosocial adjustment to TBI across different phases of injury (acute, postacute, and chronic), and (2) undertake an evaluation of efficacy, acceptability, and feasibility.Methods and analysis A three-stage mixed-methods research design will be used. The study will be undertaken across four postacute community-based neurorehabilitation and disability support services in Western Australia. Stage 1 (interviews and surveys) will use consumer-driven qualitative methodology to: (1) understand the recovery experiences and psychosocial challenges of people with TBI over key stages (acute, postacute, and chronic), and (2) identify required areas of psychosocial support to inform the psychoeducation platform development. Stage 2 (development) will use a Delphi expert consensus method to: (1) determine the final psychoeducation modules, and (2) perform acceptance testing of the myTBI platform. Finally, stage 3 (evaluation) will be a randomised stepped-wedge trial to evaluate efficacy, acceptability, and feasibility. Outcomes will be measured at baseline, postintervention, follow-up, and at final discharge from services. Change in outcomes will be analysed using multilevel mixed-effects modelling. Follow-up surveys will be conducted to evaluate acceptability and feasibility.Ethics and dissemination Ethics approval was granted by North Metropolitan Health Service Mental Health Research Ethics and Governance Office (RGS0000005877). Study findings will be relevant to clinicians, researchers, and organisations who are seeking a cost-effective solution to deliver ongoing psychoeducation and support to individuals with TBI across the recovery journey.Trial registration number ACTRN12623000990628.